Efeito do aporte térmico e da adição de arame frio na zona termicamente afetada de um aço inoxidável lean duplex soldado ao arco submerso - Danielle Silva Mendes (2018)
Duplex stainless steels combine, simultaneously, high mechanical strength and corrosion resistance. However, when welded, the ferrite-austenite ratio can increase and deleterious phases can precipitate, compromising the steel performance. A commonly adopted measure to minimize these negative effects is to strictly control the welding heat input used. However, this control often reduces the process productivity. Therefore, welding techniques that increase deposition rate with no additional heat, such as the addition of non-energized wire to the submerged arc process, may be beneficial for these materials. The present work evaluated the effect of heat input and amount of cold wire on a lean duplex stainless steel UNS S32304 welded with submerged arc with cold wire fed between two twin hot wires (SAW IceTM process). The study involved the measurement of thermal cycles and weld bead shape, and microstructural analysis of the heat affected zone (HAZ). It was verified that both heat input and cold wire addition affected HAZ thermal cycles, modifying weld bead shape and the microstructure. It was observed a reduction in the cooling rate above 1100oC, when the addition of cold wire is increased. This effect was more intense when the heat input was higher. The formation of austenite present a slight tendency to increase by the addition of cold wire. On the other hand, it was also observed that a trend of reduction of thickness of HAZ.